2020
DOI: 10.1037/rel0000275
|View full text |Cite
|
Sign up to set email alerts
|

Mediated association between spirituality and life satisfaction in chronically ill undergraduate students.

Abstract: Preservation of life satisfaction in the face of a chronic illness is of major importance for psychosocial functioning. We addressed in this study how spirituality relates to global life satisfaction in young people with chronic physical illnesses. Based on social-cognitive theory, the transactional model of stress and coping, and Pargament’s theory of religious coping, a serial mediation model with general self-efficacy beliefs and proactive coping as related linkage variables was proposed. In a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 124 publications
(198 reference statements)
2
8
0
1
Order By: Relevance
“…These results follow the preceding theoretical framework on Emmons’s motivational conceptualization of spirituality [ 34 ] and previous findings on spirituality as a resource to cope. As such, spirituality or spiritual needs respectively seem to be a resource to motivate nonreligious coping [ 79 , 80 ] as well as religious coping [ 48 , 81 ]. Focusing on religious coping, both positive and negative coping methods were activated through spiritual needs.…”
Section: Discussionmentioning
confidence: 99%
“…These results follow the preceding theoretical framework on Emmons’s motivational conceptualization of spirituality [ 34 ] and previous findings on spirituality as a resource to cope. As such, spirituality or spiritual needs respectively seem to be a resource to motivate nonreligious coping [ 79 , 80 ] as well as religious coping [ 48 , 81 ]. Focusing on religious coping, both positive and negative coping methods were activated through spiritual needs.…”
Section: Discussionmentioning
confidence: 99%
“…In line with that, Alorani and Alradayeh [48] reported a positive, significant and prevalent (r-sq=.53) correlation between spirituality and SWL among university students in Jordan. It is also important to notice that individuals with low levels of spirituality tend to develop lower levels of SWL [49] because spirituality is one of the most significant factors that help individuals cope with stressful situations [50], even among individuals with mental illness [51]. In other words, we hypothesized that spirituality played a conditional (moderation) role in the link between SWL and any of its predictors, where the positive links tend to be the strongest among individuals with higher spirituality because it interacts with how individuals value and identify their roles in the society [52].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the results of some research studies that have demonstrated that spirituality actions are directly related to the response to life satisfaction ( Lee, 2011 ; Zadworna-Cieślak, 2020 ). Furthermore, previous studies ( Wu et al., 2020 ), have pointed out that the positive practice of spirituality will bring about positive responses to life satisfaction, which implies a connection between these two factors ( Koening, 2004 ; Maier and Surzykiewicz, 2020 ).…”
Section: Discussionmentioning
confidence: 94%